Importance of city functions in the process of revitalization. Przedmieście Oławskie case study - Adamiczka, Hanna; Czarnecka, Maria; Mempel-Śnieżyk, Anna (Istota funkcji miejskich w procesie rewitalizacji. Studium przypadku Przedmieścia Oławskiego, 2018)
The paper discusses the problems connected with effects of revitalization. The authors concentrate on the differences resulting from ways as well as used base to carry out process of revitalization. The aim of the paper is assessment of the revitalized place carried out without analysis based on historical function of that place. To this end the authors used one of Wroclaw district conducted the desk research and field research. The authors used the method of observation and case studies. As a result, it can be said that revitalization process should be carried out with maintaining the historical function and the needs of inhabitants of revitalized places. The authors also refer to another example of revitalization process and compare it in the context of used ways and effects. According to the conducted research it can be said that the process of revitalization result from both legal principles and form awareness of local authorities in the context of quality of live and inhabitant needs
Biblioteka Regionalisty, 2018, Nr 18, s. 7-26
Keywords: city planning; revitalization; urban development; spatial planning; planowanie miast; rewitalizacja; rozwój miast; planowanie przestrzenne